(untitled) (International Journal of Language, Literacy and Translation, 2025)
Religious translation is a very sensitive task since it deals with God’s words and transcendentalcommandments; taking into consideration that religion is an integral part of culture puts more onus ontranslators to understand the target culture, inter alia, word’s connotations and denotations, author’sintention, context, and other factors in order to choose the most effective communication translation strategy.This study aims to conduct a bibliometric review of the most cited papers, authors and journals that areinterested in religious translation, in addition to the content analysis of the papers to identify the mostinfluential factors which affect religious terms’ translation strategies. This biblio-systematic paper addressesall the articles published in Google Scholar and SCOPUS indexed database, that have “translation,religious” in the title, and “Arabic” as a keyword (anywhere in the article). SCOPUS and google scholarsearch resulted in 17 articles related to the paper’s subject which is "the Factors Affecting Selection ofReligious Translation Strategies between Arabic and English Languages. Bibliometric review results showthat the top-cited journal is International Journal of English Linguistics. Top cited authors are ElShiekh, andM Saleh for their paper “Translation versus transliteration of religious terms in contemporary Islamicdiscourse in western communities”. Regarding publications per year, the review shows that 2016 witnessedthe highest production by six papers and that Indonesia was the most producing country. The study concludedthat the most influential factor which affects religious translation is ideology and religious belief, and themost used religious translation strategy is literal translation.